Strategi Pembelajaran IPS di Sekolah Dasar - Amini Amini; Charisa Jupni Hadifina; Maya Chintiya Devi; Muhammad Rafiqi (Departement of Mathematics Education, 2023)
Elementary School (SD) as one of the formal and tiered educational institutions at the basic education level, is quite strategic in realizing the government's mandate in the field of education. The problem in the field of education faced is the continuation of education that is less meaningful for the personal development and disposition of students, which results in the loss of personality and awareness of the true meaning of life. Morality and morality-oriented subjects as well as religious education are less given in the form of experiential exercises to become the pattern of daily life. The low learning outcomes achieved by students are caused by various factors from within the student as learners and environmental factors. Environmental factors, especially the school environment, are the learning process. A quality learning process can influence, in the sense of improving student learning achievement. These two factors (student ability and learning quality) have a straight relationship with student learning outcomes. This means that the higher the student's ability and the quality of learning, the higher the learning outcomes achieved by students. To improve the quality of learning in order to achieve educational goals, teachers occupy a very important position.